MILP-MPC for planned maneuver station-keeping and collision avoidance of GEO satellites using on-off chemical thrusters - Mohamed Karim; Mohamed Ibrahim; Hosam Hendy; Mahmoud Ashry; Yehia Z. Elhalwagy (Ain Shams Engineering Journal, 2024)
GEO satellites require precise station-keeping and ensuring collision avoidance to maintain their desired orbital positions and ensure uninterrupted communication services. However, maneuvering these satellites poses significant challenges due to various geophysical factors and orbital perturbations. This work proposes a model predictive control for planned maneuver station-keeping and collision avoidance of GEO satellites using south, east, and west maneuvers. These maneuvers have been achieved using on/off chemical thrusters with a short firing time. The station-keeping problem is reformulated as an optimization problem using mixed-integer linear programming. MILP-MPC formulation simultaneously considers multiple objectives and constraints such as fuel consumption, maneuver planning, and collision avoidance for mitigating collision risks. Simulation results demonstrate the effectiveness of the proposed MILP-MPC framework compared to the real-time telemetry in achieving accurate station-keeping and collision-free operation while optimizing fuel consumption. The proposed controller increases the satellite lifetime by reducing the thruster firing time.